2014
DOI: 10.1016/j.proeng.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Investigations and Approaches on Material Flow of Non-uniform Arranged Cavities in Sheet Bulk Metal Forming Processes

Abstract: To encounter new challenges regarding the economic an ecological aspects of the forming of functional components, sheet bulk metal forming has been introduced as a new approach. An important aspect for the successful use of such processes is the control of the complex material flow. At the moment there is knowledge on the material flow in uniform arranged cavities, as well as on possibilities which enable its control. However there is no data on the behavior of the material flow in non-uniform arranged cavitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In the example above, the maximum possible reinforcement regarding the ultimate compressive strength of the tool steel ASP2023 (1.3344) is utilized. However, simulated results with a validated simulation model [12] show, that tensile stresses can locally reach values of up to 1,500 MPa despite using the relatively low strength steel DC04 of t 0 = 3 mm, which is the maximum sheet thickness formed by this process, initial thickness and a punch stroke of t = 2.7 mm. Hence, especially with high strength materials, available tool load will limit the total process stroke and therefore the maximum possible element dimensions.…”
Section: Forward Extrusionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the example above, the maximum possible reinforcement regarding the ultimate compressive strength of the tool steel ASP2023 (1.3344) is utilized. However, simulated results with a validated simulation model [12] show, that tensile stresses can locally reach values of up to 1,500 MPa despite using the relatively low strength steel DC04 of t 0 = 3 mm, which is the maximum sheet thickness formed by this process, initial thickness and a punch stroke of t = 2.7 mm. Hence, especially with high strength materials, available tool load will limit the total process stroke and therefore the maximum possible element dimensions.…”
Section: Forward Extrusionmentioning
confidence: 98%
“…This process variant has been firstly described in reference [11] in combination with deep drawing and has been extended in reference [12] with the introduction of geometrically differing elements to increase the components complexity. In order to perform the forming operation, a circular blank is placed centrally on the die.…”
Section: Forward Extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes are modelled by holding planes on the top and bottom of the dies and symmetry planes at the edge of the 17°s egments. This reduces the calculation time while the findings and quality remain constant [19]. One challenge of modelling SBMF processes in simulation is the typical scale conflict between functional-element dimensions and the overall size of the workpiece [19].…”
Section: Setupmentioning
confidence: 99%
“…The radial material flow leads to a bulging of the sheet in the centre and simultaneous insufficient filling of the tool moulds. Current research revealed that this effect is dependent on the chosen geometry of the cavity in question, as well as on the arrangement of the moulds [24].…”
Section: Boundary Conditions For Presented Sheet-bulk Metal Forming Pmentioning
confidence: 99%